Pre‐implementation formative evaluation of cooperative pain education and self‐management expanding treatment for real‐world access: A pragmatic pain trial. Issue 4 (29th December 2022) - Mattocks, Kristin M.; LaChappelle, Kathryn M.; Krein, Sarah L.; DeBar, Lynn L.; Martino, Steve; Edmond, Sara; Ankawi, Brett; MacLean, R. Ross; Higgins, Diana M.; Murphy, Jennifer L.; Cooper, Emily; Heapy, Alicia A.
Abstract: Objective: Cognitive behavioral therapy for chronic pain (CBT‐CP) is an evidence‐based treatment for improving functioning and pain intensity for people with chronic pain with extensive evidence of effectiveness. However, there has been relatively little investigation of the factors associated with successful implementation and uptake of CBT‐CP, particularly clinician and system level factors. This formative evaluation examined barriers and facilitators to the successful implementation and uptake of CBT‐CP from the perspective of CBT‐CP clinicians and referring primary care clinicians. Methods: Qualitative interviews guided by the Consolidated Framework for Implementation Research were conducted at nine geographically diverse Veterans Affairs sites as part of a pragmatic clinical trial comparing synchronous, clinician‐delivered CBT‐CP and remotely delivered, technology‐assisted CBT‐CP. Analysis was informed by a grounded theory approach. Results: Twenty‐six clinicians (CBT‐CP clinicians = 17, primary care clinicians = 9) from nine VA medical centers participated in individual qualitative interviews conducted by telephone from April 2019 to August 2020. Four themes emerged in the qualitative interviews: (1) the complexity and variability of referral pathways across sites, (2) referring clinician's lack of knowledge about CBT‐CP, (3) referring clinician's difficulty identifying suitable candidates for CBT‐CP, and (4) preference for interventions that can be completed from home. Conclusions: This formative evaluation identified clinician and system barriers to widespread implementation of CBT‐CP and allowed for refinement of the subsequent implementation of two forms of CBT‐CP in an ongoing pragmatic trial. Identification of relative difference in barriers and facilitators in the two forms of CBT‐CP may emerge more clearly in a pragmatic trial that evaluates how treatments perform in real‐world settings and may provide important information to guide future system‐wide implementation efforts.